Dietary, Metabolic, and Potentially Environmental Modulation of the Lysine Acetylation Machinery - Go-Woon Kim; Goran Gocevski; Chao-Jung Wu; Xiang-Jiao Yang (International Journal of Cell Biology)
Healthy lifestyles and environment produce a good state of health. A number of scientific studies support the notion that external stimuli regulate an individual's epigenomic profile. Epigenetic changes play a key role in defining gene expression patterns under both normal and pathological conditions. As a major posttranslational modification, lysine (K) acetylation has received much attention, owing largely to its significant effects on chromatin dynamics and other cellular processes across species. Lysine acetyltransferases and deacetylases, two opposing families of enzymes governing K-acetylation, have been intimately linked to cancer and other diseases. These enzymes have been pursued by vigorous efforts for therapeutic development in the past 15 years or so. Interestingly, certain dietary components have been found to modulate acetylation levels in vivo. Here we review dietary, metabolic, and environmental modulators of the K-acetylation machinery and discuss how they may be of potential value in the context of disease prevention.